Transcriptional profiling of Medicago truncatula during Erysiphe pisi infection - Curto Rubio, Miguel; Krajinski, Franziska; Schlereth, Armin; Rubiales Olmedo, Diego (Frontiers in Plant Science, 2015)
Resistance to powdery mildew has been studied in a number of plant species, yet the molecular mechanisms remain largely unknown. Transcription factors (TFs) play a critical role in the plant defense response by regulating the transcriptional machinery which coordinates the expression of a large group of genes involved in plant defense. Using high-throughput quantitative real-time PCR (qPCR) technology more than 1,000 Medicago truncatula TFs were screened in a pair of susceptible and resistant genotypes of M. truncatula after 4 h of Erysiphe pisi infection. Seventy nine TF genes, belonging to 33 families showed a significant transcriptional change in response to E. pisi infection. Forty eight TF genes were differentially expressed in the resistant genotypes compared to the susceptible one in response to E. pisi infection, including pathogenesis-related transcriptional factors, AP2/EREBP (APETALA2/ETHYLENE-RESPONSIVE ELEMENT BINDING FACTORS), WRKY (highly conserved WRKYGQK amino-acid sequence), MYB (Myeloblastoma), homeodomain (HD) and zinc finger C2C2 (CYS2-CYS2), C2H2, (CYS2-HIS2), LIM (Lin-11, Isl-1, Mec-3) gene families, which are involved in known defense responses. Our results suggest that these TF genes are among the E. pisi responsive genes in resistant M. truncatula that may constitute a regulatory network which controls the transcriptional changes in defense genes involved in resistance to E. pisi.